The Role Of Psychological And Social Factors In The Caesarean Section Birth Preferences Of Women Who Exercise - Sevil, Ümran; Yücel, Ali Serdar; Çatıkkaş, Fatih; Özpınar, Saliha; Öztaş, Dilek; Korkmaz, Murat (METİN YAMAN, 2025)
Objective: This study aims to identify the psychological, social, demographic, and environmental factors that influence the preference for caesarean section among women who exercise. Scope: The study focuses solely on caesarean section, with normal delivery being evaluated for comparison purposes. Multidimensional factors such as psychological status, social media usage, previous birth experiences, and socio-economic variables were analyzed within the scope of the study. Method: The scale used in the study consists of a two-part questionnaire. This scale is a validated and reliable questionnaire. The first part of the questionnaire includes demographic information and lifestyle, while the second part includes women's attitudes towards caesarean and normal birth. The research was conducted in Istanbul, Izmir, Ankara, Antalya, and Elazığ provinces of Turkey. The study was conducted using a convenience sampling method based on participant eligibility. The data obtained were analyzed using various statistical methods, using ANOVA, t-test, Mann-Whitney U test, Spearman correlation, factor analysis, and logistic regression. Results: It was found that the preference for caesarean section was based not only on medical reasons but also on psychological and social factors. In particular, attitudes toward cesarean section differed significantly among women with psychological problems and those with a history of miscarriage or abortion. Additionally, social media usage had a strong influence on the preference for cesarean section. On the other hand, exercise habits and certain socioeconomic variables did not have a significant effect on the preference for cesarean section. In conclusion, the decision to undergo a cesarean section is shaped by a combination of multidimensional factors. In this context, health policies should be structured to support individuals in terms of psychological support, access to information, and social environment.

Amaç: Bu çalışma, spor yapan kadınların sezaryen doğum tercihini etkileyen psikolojik, sosyal, demografik ve çevresel faktörleri saptanmasını amaçlamaktadır. Kapsam: Çalışma yalnızca sezaryen doğuma odaklanmış, normal doğum tercihi karşılaştırma amacıyla değerlendirilmiştir. Psikolojik durum, sosyal medya kullanımı, geçmiş doğum deneyimleri ve sosyoekonomik değişkenler gibi çok boyutlu etkenler çalışma kapsamında analiz edilmiştir. Yöntem: Çalışmada kullanılan ölçek iki bölümden oluşan bir anketten oluşmaktadır. Bu ölçek geçerlilik ve güvenirliliği sağlanmış bir ankettir. Anketin İlk bölümde demografik bilgiler ve yaşam tarzı, ikinci bölümde ise kadınların sezaryen ve normal doğuma yönelik tutumları yer almaktadır. Araştırma Türkiye evreni İstanbul, İzmir, Ankara, Antalya ve Elazığ illeri örneklemi ile gerçekleştirilmiştir. Çalışma katılımcı uygunluğuna dayalı kolayda örnekleme yöntemi ile uygulanmıştır. Elde edilen veriler, ANOVA, t-testi, Mann-Whitney U testi, Spearman korelasyonu, faktör analizi ve lojistik regresyon gibi çeşitli istatistiksel yöntemler kullanılarak analiz edilmiştir. Bulgular: Sezaryen tercihinin yalnızca tıbbi gerekçeler ile değil, aynı zamanda psikolojik ve sosyal nedenlere dayandığı saptanmıştır. Özellikle psikolojik sorun yaşayan kadınlar ile geçmişte düşük veya kürtaj deneyimi olan bireylerde sezaryene yönelik tutumlar anlamlı düzeyde farklılık göstermektedir. Ayrıca sosyal medya kullanımı da sezaryen tercihi üzerinde güçlü bir etkisi bulunmaktadır. Bir diğer yandan spor yapma alışkanlığı ve bazı sosyoekonomik değişkenlerin sezaryen tercihi üzerinde belirgin bir etkisi bulunmamıştır. Sonuç olarak, sezaryen doğum kararı çok boyutlu etkenlerin bir araya gelmesiyle şekillenmektedir. Bu doğrultuda bakıldığında sağlık politikalarının bireylerin psikolojik destek, bilgiye erişim ve sosyal çevre gibi faktörler açısından desteklenmesini sağlayacak şekilde yapılandırılması gerekmektedir.
Spor Yapan Kadınların Sezaryen Doğum Tercihlerinde Psikolojik Ve Sosyal Etkenlerin Rolü
Keywords: Physical Activity and Health; Fiziksel Aktivite ve Sağlık